Mathematics and medicine. Test reduction: III-Practical applications. Issue 6241 (6th September 1980) - Card, W I; Emerson, P A
Abstract : While there is no generally applicable method of test reduction, ways in which the problem can be tackled can usually be suggested. These include the examination of error rates of tests and the use of current statistical methods. When the cost-effectiveness of some more expensive test has to be measured, a model of the decision problem needs to be developed, with an attempted estimation of the values or utilities of the states of health that result from treatment.